Reproductive and sexual rights: Charting the course of transnational women's NGOs - Rosalind P. Petchesky (United Nations Research Institute for Social Development (UNRISD), 2000)
This paper critically examines the role that transnational women's NGOs played in the 1990s in the creation and implementation of international agreements related to reproductive and sexual rights. Its focus throughout is twofold. First, it explores the multiple ways in which reproductive and sexual rights intersect with, and are embraced within, a wide range of health, human rights, social and gender justice and human development issues. Second, it uses this inquiry to rethink the complex political dynamics in which transnational women's NGOs find themselves, as they manoeuvre within a globalizing yet deeply divided and grossly inequitable world. These dynamics encompass a double and precarious positioning. On the one hand, feminist groups have had a major impact at both international and national levels in shifting dominant discourses about reproduction, population and sexuality in a direction that puts the ends of women's health and empowerment above that of reducing population growth. This is a major historical achievement and a mark of the power of transnational women's NGOs. On the other hand, the translation of this discursive shift into effective policies and programmes has been seriously limited by global economic processes and religious and cultural forces whose institutional power is far greater than any that feminist groups could possibly attain at this juncture. It has also been limited, however, by internal divisions and strategic short-sightedness among the women's groups themselves. The paper assesses recent successes and limitations of women's movements as agents of change in the international arena by focusing particularly on the work of organizations and coalitions active in the field of reproductive and sexual health and rights. Building on previous research, it analyses the 'fault lines' between reproductive and sexual health/rights and their necessary economic, social and cultural enabling conditions. Groups seeking to implement reproductive and sexual rights for women and young people have long had to confront macroeconomic, fundamentalist and neo-Malthusian agendas that perpetuate gender, race and class inequalities and thus impede concrete implementation of those rights for the vast majority. Recently, however, the project of transforming these conditions has been complicated by several additional trends. These include: (1) ongoing economic crises that simultaneously call into question and provide an occasion for reforming structural adjustment policies and public sector cuts imposed by international lenders; (2) health reform plans that stress cost-recovery measures such as user fees; (3) the abdication by national governments of their responsibility to provide social services in basic areas such as health care and education; and (4) the tendency for diverse actors who lack any political accountability-such as fundamentalist religious groups, commercial businesses and non-profit NGOs-to fill the gap. The body of the paper is organized into four sections. Section I looks at the broad vision of reproductive and sexual health and rights developed by feminists of the North and the South over the past three decades. The discussion here emphasizes the holistic perspective linking three components: health, development and human rights. It also shows how such thinking seriously challenges approaches that dichotomize rights and needs, individuals and communities, by investigating the necessary links, in both ethics and politics, between basic needs and fundamental human rights. Section II offers an overview of the United Nations conferences of the 1990s in order to assess how and where the women's coalition succeeded in infusing its perspectives on reproductive and sexual rights into the conference documents, and where and why it failed. Focusing mainly on the International Conference on Population and Development (ICPD) in Cairo, the Fourth World Conference on Women in Beijing and the World Summit for Social Development in Copenhagen, the analysis contrasts feminist perspectives and strategies with those of two other major 'stakeholders' who have attempted to shape the dominant international discourses and policies around reproductive and sexual health: fundamentalist groups, especially the Vatican, and mainstream population and family planning organizations. The success of these two groups in also influencing the conference documents at strategic points, as well as the weak political process of the United Nations itself, render those documents fragile and contradictory despite their groundbreaking advances. Section III begins with an overview of globalization, macroeconomic policies affecting social services and recent trends in health sector reform. Within the context of diminished state responsibilities and what I call 'the many faces of privatization,' the paper looks at the efforts of women's NGOs to hold their governments accountable for international commitments, implement the provisions of the ICPD Programme of Action, and transform reproductive and sexual health/rights into concrete policy. In most cases, economic constraints, gaps in resources and cuts in services-sometimes compounded by the resurgence of fundamentalist movements-form the backdrop to women's activism. In some contexts, however, women's NGOs are making important changes in national policy despite the disabling environment, and occasionally (for example in Brazil) are creating new and promising models of civil society-government co-operation. Finally, the last section examines recent concerns that NGO activism may become merely another link in the chain of privatization that further weakens state power, and thus state responsibility, in the era of globalization. I conclude that the participation by women's health NGOs in both the United Nations conferences and the national-level implementation processes has on the whole had beneficial outcomes. Both experiences have led to a broader understanding of the necessity for profound structural changes in macroeconomic policies and the system of global governance, if reproductive and sexual rights are to become a reality for all. However, this holistic vision still lacks a commensurate strategy-including stronger coalitions with other social movements; measures to counter or regulate the privatization of social services, even when performed by women's groups; and effective mechanisms for civil society organizations to monitor and transform macroeconomic policies and institutions. Such a strategy is indispensable to creating the necessary enabling environment for people-centred health care.
Keywords: 330